2004
DOI: 10.2320/matertrans.45.307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Microstructure and Mechanical Properties of Stoichiometric SiC/SiC Composites

Abstract: Polymer impregnation and pyrolysis (PIP) is one of the most attractive fabrication processes for silicon carbide (SiC) composites due to the shape flexibility, mass production and relatively low cost. In particular, advanced PIP SiC/SiC composite with high-crystallinity and nearstoichiometric composition is expected to have superior thermo-mechanical properties including good oxidation resistance, due to the reduction of impurities and well-organized crystal structure. Additionally, by applying a thin carbon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1). State of the art in SiC/SiC composites has solved most of the potential issues of near-net shaping and machining, joining technology and evaluation technology [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. There are no doubts that SiC/SiC composites are at the forefront of advanced materials technology and prime candidates for structural material in severe environments.…”
Section: Introductionmentioning
confidence: 98%
“…1). State of the art in SiC/SiC composites has solved most of the potential issues of near-net shaping and machining, joining technology and evaluation technology [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. There are no doubts that SiC/SiC composites are at the forefront of advanced materials technology and prime candidates for structural material in severe environments.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study revealed the width effect on tensile strength of various types of SiC/SiC composites. 24) In that report, a three directionally woven TyrannoÔ-SA fiber reinforced composite made by the modified PIP process 25) and a cross-plied TyrannoÔ-SA fiber reinforced laminate composite made by the nano-infiltration transient eutectic phase (NITE) process 26,27) were evaluated. Both composites featured a highly crystalline and near stoichiometric SiC matrix.…”
Section: Generality Of Specimen Size Effectmentioning
confidence: 99%
“…However, small pores were distributed in the PIP–SiC matrix as shown in Table I, resulting in a comparably lower density of ∼2.1 g/cm 3 . Details of the PIP process are described in Nozawa et al 17 …”
Section: Methodsmentioning
confidence: 99%